Adverse selection as ethical and social issue of applying genetic testing in insurance - Arych, Mykhailo; Levon, Mariia (My University, 2020)
The review of previous research results shows that in most cases the scientists and researchers have concentrated on discussing different aspects of human genetics and insurance peculiarities, such as: use by insurer, risk classification, genetic discrimination, adverse selection, as well as technical, social and ethical issues. Hence, one of the main risks for insurance companies is related to using genetic testing information in the underwriting process and is known as adverse selection. Also, it shows the tendency of some individuals to buy new insurance policies or to renew insurance more frequently and for larger insurance coverage. Огляд попередніх результатів досліджень показує, що в більшості випадків вчені та дослідники зосереджувались на обговоренні різних аспектів людської генетики та особливостей страхування, таких як: використання страховиком, класифікація ризиків, генетична дискримінація, несприятливий відбір, а також технічні, соціальні та етичні проблеми. Отже, один із основних ризиків для страхових компаній пов'язаний із використанням інформації про генетичне тестування в процесі андеррайтингу і відомий як несприятливий відбір. Крім того, це свідчить про тенденцію деяких осіб купувати нові страхові поліси або частіше поновлювати страхування та збільшувати страхове покриття.
Keywords: кафедра фінансів; insurance; insurance market; genetic research; genetic discrimination; efficiency; ефективність; страхування; страховий ринок; генетичні дослідження; генетична дискримінація